Types of perception of work-life balance among MZ generation nurses: A Q methodology approach - Hwa Mi Yang; Byeong Jun Park; Young Eun Jang; Park Jung Sun (Nursing Practice Today)
Background & Aims: Research on the types of work-life balance perceptions among MZ generation nurses is essential for improving collaboration and communication within organizations. The study aimed to identify the types of role perceptions regarding work-life balance (WLB) among MZ generation nurses. Materials & Methods: The Q methodology was applied, selecting 36 Q samples from a population of 190, which were extracted from literature and in-depth clinical interviews with preceptors, new nurses, and nursing managers. The P sample consisted of 40 MZ generation nurses who had experience as preceptors regarding work-life balance. The Q samples were classified into a quasi-normal distribution frame and measured on a nine-point scale. Data were analyzed using the PQ Method program. Results: Q factor analysis of the subjective perceptions of MZ generation nurses regarding WLB revealed four types: 'Organizational-Culture-Oriented,' 'Personal-Goal-Oriented,' 'Organizational-Culture-Dissatisfied,' and 'Emotional -Stability-Oriented.' These four types explained 54.1% of the total variance. Conclusion: The findings suggest that MZ generation nurses prioritize mental satisfaction and quality of life over economic compensation. Therefore, organizations can improve job satisfaction and organizational commitment among nurses by providing multidimensional support that reflects their diverse needs.